Polyploidy did not predate the evolution of nodulation in all legumes. - Steven B Cannon; Dan Ilut; Andrew D Farmer; Sonja L Maki; Gregory D May; Susan R Singer; Jeff J Doyle (PLoS ONE, 2010)
BACKGROUND: Several lines of evidence indicate that polyploidy occurred by around 54 million years ago, early in the history of legume evolution, but it has not been known whether this event was confined to the papilionoid subfamily (Papilionoideae; e.g. beans, medics, lupins) or occurred earlier. Determining the timing of the polyploidy event is important for understanding whether polyploidy might have contributed to rapid diversification and radiation of the legumes near the origin of the family; and whether polyploidy might have provided genetic material that enabled the evolution of a novel organ, the nitrogen-fixing nodule. Although symbioses with nitrogen-fixing partners have evolved in several lineages in the rosid I clade, nodules are widespread only in legume taxa, being nearly universal in the papilionoids and in the mimosoid subfamily (e.g., mimosas, acacias)--which diverged from the papilionoid legumes around 58 million years ago, soon after the origin of the legumes. METHODOLOGY/PRINCIPAL FINDINGS: Using transcriptome sequence data from Chamaecrista fasciculata, a nodulating member of the mimosoid clade, we tested whether this species underwent polyploidy within the timeframe of legume diversification. Analysis of gene family branching orders and synonymous-site divergence data from C. fasciculata, Glycine max (soybean), Medicago truncatula, and Vitis vinifera (grape; an outgroup to the rosid taxa) establish that the polyploidy event known from soybean and Medicago occurred after the separation of the mimosoid and papilionoid clades, and at or shortly before the Papilionoideae radiation. CONCLUSIONS: The ancestral legume genome was not fundamentally polyploid. Moreover, because there has not been an independent instance of polyploidy in the Chamaecrista lineage there is no necessary connection between polyploidy and nodulation in legumes. Chamaecrista may serve as a useful model in the legumes that lacks a paleopolyploid history, at least relative to the widely studied papilionoid models.